A sense of place, many times over ‐ pattern formation and evolution of repetitive morphological structures. Issue 3 (22nd November 2019) - Grall, Emmanuelle; Tschopp, Patrick
Abstract: Fifty years ago, Lewis Wolpert introduced the concept of "positional information" to explain how patterns form in a multicellular embryonic field. Using morphogen gradients, whose continuous distributions of positional values are discretized via thresholds into distinct cellular states, he provided, at the theoretical level, an elegant solution to the "French Flag problem." In the intervening years, many experimental studies have lent support to Wolpert's ideas. However, the embryonic patterning of highly repetitive morphological structures, as often occurring in nature, can reveal limitations in the strict implementation of his initial theory, given the number of distinct threshold values that would have to be specified. Here, we review how positional information is complemented to circumvent these inadequacies, to accommodate tissue growth and pattern periodicity. In particular, we focus on functional anatomical assemblies composed of such structures, like the vertebrate spine or tetrapod digits, where the resulting segmented architecture is intrinsically linked to periodic pattern formation and unidirectional growth. These systems integrate positional information and growth with additional patterning cues that, we suggest, increase robustness and evolvability. We discuss different experimental and theoretical models to study such patterning systems, and how the underlying processes are modulated over evolutionary timescales to enable morphological diversification. Key Findings: Through a combination of positional information, directed growth and additional periodic patterning modules, repetitive morphological structures can be specified during development, in a robust, yet flexible manner.